Pengaruh Model Pembelajaran Small Group Discussion menggunakan Media Audiovisual terhadap Hasil Belajar IPA Kelas V Sekolah Dasar - Dewi Fitriani (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study seeks to determine the effect of the small group discussion learning model with using audiovisual media in class V Elementary School. This study used a quasi-experimental qualitative research approach with 40 class X students at SD IT Adzkia 3 as subjects. The results of this study found that the learning model was small group discussion using media audio visual influential to class science learning outcomes VA Class And VB Class SDIT Adzkia 3. This is reflected by the t test (Independent Sample Test)which reflects the value of t = 3.701 and a significance (Sig) of 0.001 < 0.005 so can concluded Ha is accepted and H0 rejected. This research has proven that the application of small group discussions using audiovisual media is very important in improving the quality of student learning so that it is effective for teachers to apply it so that science learning on ecosystem material runs optimally.